2022
DOI: 10.1111/anae.15909
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided genicular nerves block vs. local infiltration analgesia for total knee arthroplasty: a randomised controlled non‐inferiority trial

Abstract: Genicular nerves block is a promising technique to treat acute postoperative pain in total knee arthroplasty. Similar to surgeon-administered local infiltration analgesia, it targets sensory branches from the knee capsule, but through a selective ultrasound-guided injection that reduces local anaesthetic dose (150 ml ropivacaine 0.2% with local infiltration analgesia vs. 20 ml with genicular nerves block). This randomised non-inferiority trial compared the analgesic efficacy of genicular nerves block vs. local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…† : Significantly different from Preoperative, # : Significantly different from 30th day. used and the level of pain in the first 24 hours were significantly lower in the GNB group, and concluded that GNB was a good alternative for pain management in TKA 22 . In another similar study, Pierangela et al found GNB to be a reasonable alternative in TKA, in line with the results of this study 23 .…”
Section: Discussionmentioning
confidence: 91%
“…† : Significantly different from Preoperative, # : Significantly different from 30th day. used and the level of pain in the first 24 hours were significantly lower in the GNB group, and concluded that GNB was a good alternative for pain management in TKA 22 . In another similar study, Pierangela et al found GNB to be a reasonable alternative in TKA, in line with the results of this study 23 .…”
Section: Discussionmentioning
confidence: 91%
“…GNB is used for the treatment of persistent pain after osteoarthritis and total knee arthroplasty [3,4] to reduce chronic postoperative pain. GNB selectively blocks the articular branch of the anterior capsule of the knee, and it has been reported to result in lower pain scores at 24 hours after surgery and greatly reduced use of local anesthetic solutions than local infiltration analgesia [5,6]. Although the genicular nerves block is injected at five points, its position is superficial, and the bony landmarks are obvious, so the operation is simple, and the time required is short (about 6 minutes).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, nerve blocks are free of these risks, making QLB a promising method for clinical application. With advancements in technology, the proficiency of anesthesiologists in using ultrasound has also increased, making ultrasound-guided nerve blocks more accurate, less invasive, and more beneficial for patients 5 . Because there is no obvious breakthrough sensation, QLB can only be performed using ultrasound-guided puncture techniques.…”
Section: Introductionmentioning
confidence: 99%